Role of physique and physical fitness in the balance of Korean national snowboard athletes - Jeon, Y.; Eom, K. (Journal of Exercise Science & Fitness, 2021)
The objective of this study is to understand the relationship between physique, physical fitness, and balance performance for snowboard athletes. Methods: We considered all Korean national snowboard athletes (n = 9 with 6 males and 3 females, age = 17.44 ± 4.42), who have an experience of competition at continental cup level, to measure their physique, physical fitness, and (both static and dynamic) balance. Static balance was evaluated based on one-legged standing, while dynamic balance was estimated using a stability platform. Results: Static balance is strongly correlated (p < 0.05) with circumference of the left lower leg (34.49 ± 2.42 cm; p = 0.68), sit-up (57.56 ± 8.8; p = 0.72), sargent jump (50.22 ± 11.78 cm; p = 0.67), strength of bench press (39.11 ± 17.73 kg; p = 0.67), angle of left ankle dorsiflexion (73.78 ± 7.86°; p = 0.77), average extension strength at 180° for left knee (321 ± 63.95 %BW; p = 0.77) and right knee (337 ± 60.32 %BW; p = 0.77), and right knee peak flexion strength at 60° (148 ± 25.61 %BW; p = 0.73). Center dynamic balance is negatively correlated with circumference of the right lower leg (34.63 ± 2.38 cm; p = -0.67, p < 0.05), while right dynamic balance is positively correlated with left ankle flexion (148.44 ± 5.20°; p = 0.78, p < 0.05). Conclusion: Static balance is related to core muscle endurance and power, ankle flexibility, and knee stability, while dynamic balance is negatively correlated with circumference of the most frequently used lower leg (i.e., the leg dominating the snowboarding stance). The relationship between physique, physical fitness, and balance provides an insight into improving the balance performance of elite snowboard athletes through a training program that can affect the physique and physical fitness factors related to balance.